Interaction between chromaffin and sustentacular cells in adrenal medulla of viscacha (Lagostomus maximus maximus) - Rodríguez, H. (2007)
New evidence provides valuable information about the participation of sustentacular cells in chromaffin cell catecholamine secretion. In this process, calcium ions play an important role. It has been shown that there is an intense ionic traffic between both types of cells. Moreover, sustentacular cells take an active part in calcium metabolism, regulating levels of the ion and indirectly, the synthesis and release of catecholamines. This background information encouraged us to study the sustentacular population of Lagostomus adrenal medulla and its morphologic relationship with the chromaffin population. The animals were captured, transported to the animal facilities, anaesthetized and killed. The adrenal gland was processed by immunohistochemistry using antiserum against S-100 (subunit α and β), a specific marker. Through the morphological and immunohistochemical study, it was found that there are sustentacular cells in deferent regions of adrenal medulla, mainly in the basal zone of chromaffin cells, which constitute the glomerular structure around blood capillaries. Cytoplasmic extentions of sustentacular cells penetrate into chromaffin cells and make contact with the basal membrane of the capillary endothelium. The relationship among chromaffin cells, capillaries and sustentacular cells suggests that they may intervene actively in the adrenal medulla metabolism.